1989
DOI: 10.1007/bf03160048
|View full text |Cite
|
Sign up to set email alerts
|

Gangliosides in the brain in adult Down’s syndrome and Alzheimer’s disease

Abstract: Quantitative analysis of total gangliosides and of ganglioside composition by HPTLC has been carried out on the gray matter of frontal cerebral cortex of six brains from Down's syndrome (DS) adults, six age-matched controls, six Alzheimer's disease (AD) adults, and six controls matched for age with the AD brains, as well as on three DS and six control cerebellum specimens. In addition, the analyses were carried out on specimens of corpus callosum of five adult DS and five control brains. No abnormalities were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…In contrast to the robust changes in the cortex, only slight changes in the ganglioside pattern were found in the cerebellum in the PSEN1 and APP/PSEN1 mutant lines (40). Alterations in cerebellar gangliosides have not been reported in the cerebellum of AD brains, although b-series cerebellar gangliosides are reduced in normal aging (29) and a reduction in total cerebellar gangliosides has been reported in patients with DS (25). Recently, Bernardo et al (40) reported ganglioside alterations in mixed cortical/ hippocampal tissue of mice lacking St8sia1, the gene that codes for GD3 synthase (GD3S), and in a doubletransgenic (APP Swe /PSEN1De9) mouse model of AD crossbred with GD3S 2/2 mice.…”
Section: Ganglioside Metabolism In Admentioning
confidence: 82%
See 2 more Smart Citations
“…In contrast to the robust changes in the cortex, only slight changes in the ganglioside pattern were found in the cerebellum in the PSEN1 and APP/PSEN1 mutant lines (40). Alterations in cerebellar gangliosides have not been reported in the cerebellum of AD brains, although b-series cerebellar gangliosides are reduced in normal aging (29) and a reduction in total cerebellar gangliosides has been reported in patients with DS (25). Recently, Bernardo et al (40) reported ganglioside alterations in mixed cortical/ hippocampal tissue of mice lacking St8sia1, the gene that codes for GD3 synthase (GD3S), and in a doubletransgenic (APP Swe /PSEN1De9) mouse model of AD crossbred with GD3S 2/2 mice.…”
Section: Ganglioside Metabolism In Admentioning
confidence: 82%
“…Figure 1 shows the structure and metabolism of gangliosides in the brain. Several earlier studies showed alterations in ganglioside metabolism in AD brain (23)(24)(25)(26)(27)(28)(29). This is manifested as reductions in gangliosides in the majority of brain regions, including the cerebral cortex, hippocampus, basal telencephalon, and frontal white matter, and especially in the frontal cortex and white matter (24).…”
Section: Ganglioside Metabolism In Admentioning
confidence: 95%
See 1 more Smart Citation
“…The patterns of ganglioside alterations in AD are very complex and differ according to age of onset and type of mutation, suggesting that different GSL-regulated events contribute to the onset of different AD forms. However, a consistent finding was a reduced ganglioside concentration (associated with altered ratios of a-series to b-series gangliosides) in the majority of brain regions of AD and dementia of the Alzheimer type-affected patients [101,102,[226][227][228][229][230] with respect to age-matched healthy controls. A reduced sulfatide content in AD post-mortem brain samples has also been reported [231,232].…”
Section: Sphingolipid Storage Diseasesmentioning
confidence: 99%
“…A series of biochemical findings, including deteriorated glucose [3][4][5][6][7][8][9], lipid [10][11][12], purine [13][14][15], methionine/homocysteine [16][17][18] and folate [17,[19][20] metabolism have been reported but no systematic study on metabolic differences in fetal or adult DS brain has been conducted so far.…”
Section: Introductionmentioning
confidence: 99%